2014
DOI: 10.1371/journal.pone.0108265
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Polycomb Proteins EZH2, BMI1 and SUZ12 and Histone Modification H3K27me3 in Colorectal Cancer

Abstract: Numerous changes in epigenetic mechanisms have been described in various types of tumors. In search for new biomarkers, we investigated the expression of Polycomb-group (PcG) proteins EZH2, BMI1 and SUZ12 and associated histone modification H3K27me3 in colorectal cancer. Nuclear expression of PcG proteins and histone modification H3K27me3 were immunohistochemically (IHC) stained on a tissue microarray (TMA), including 247 tumor tissues and 47 normal tissues, and scored using the semi-automated Ariol system. Tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 41 publications
1
62
0
7
Order By: Relevance
“…46,47 However, high BMI1 expression is also correlated with a better prognosis compared to patients with low expression. 48 By combing several biomarkers with the BMI1 expression, prognostic stratification is improved. 48 In addition, another recent study reported that patients with decreased postoperative plasma mRNA levels of BMI1 compared to patients with increased postoperative mRNA levels correlated with a favorable prognosis in CRC.…”
Section: Bmi1mentioning
confidence: 99%
See 2 more Smart Citations
“…46,47 However, high BMI1 expression is also correlated with a better prognosis compared to patients with low expression. 48 By combing several biomarkers with the BMI1 expression, prognostic stratification is improved. 48 In addition, another recent study reported that patients with decreased postoperative plasma mRNA levels of BMI1 compared to patients with increased postoperative mRNA levels correlated with a favorable prognosis in CRC.…”
Section: Bmi1mentioning
confidence: 99%
“…48 By combing several biomarkers with the BMI1 expression, prognostic stratification is improved. 48 In addition, another recent study reported that patients with decreased postoperative plasma mRNA levels of BMI1 compared to patients with increased postoperative mRNA levels correlated with a favorable prognosis in CRC. 49 These studies suggest that BMI1 may be of relevance as a prognostic indicator in CRC.…”
Section: Bmi1mentioning
confidence: 99%
See 1 more Smart Citation
“…Enhancer of zeste homology 2 (EZH2) is the catalytic subunit of polycomb repressive complex 2, which represses gene expression by generating a methylated epigenetic mark at Lys27 of histone H3 (H3K27me3) [7, 8]. It appears that EZH2 is up-regulated in a variety of human malignancies, including breast, colorectal, prostate, cervical and lung cancers, as well as sarcoma and glioblastoma, where its expression is associated with cancer initiation, progression, metastasis and prognosis [9, 10].…”
Section: Introductionmentioning
confidence: 99%
“…In breast cancer, overexpression of BMI1 was reported to have different influences on patient prognosis by Pietersen et al and BMI1 was found to have no prognostic value in urothelial carcinoma of the bladder 45,48. In contrast, survival data from Benard et al also showed that high expression of BMI1 was associated with better patient survival and longer recurrence-free periods, compared to prostate cancer patients with low BMI1 expression 10. Single-institution-based research with limited sample sizes might account for these inconsistent findings, while tissue/organ specificity of oncogenetic BMI1 activation needs further investigation as a priority.…”
Section: Future Challengesmentioning
confidence: 98%